Chlorine Corrosion of Blast Furnace Gas Pipelines: Analysis from Thermal Perspective - Sun, Wenqiang; Xu, Xiandong; Zhang, Yan; Wu, Jianzhong (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
With the broad application of dry dedusting of blast furnace gas (BFG), the issue of BFG pipeline corrosion comes up because of chlorine in the BFG. Existing methods in preventing the corrosion, such as spraying alkali or installing corrosion-resistant materials, require a significant amount of investment. This paper conducted a novel thermal analysis of the corrosion mechanism to support the study on corrosion prevention without using additional materials. Firstly, thermal models were established to reflect the relationships among the amount of condensation water, the mass transfer rate, the concentration of chloride ion and the ambient temperature. Secondly, the relationship between BFG temperature and the corrosion rate was obtained via a cyclic exposure experiment. Key factors that affect the pipeline corrosion under various BFG temperatures were identified. Finally, a control scheme of the BFG temperature was proposed to avoid the chlorine corrosion.